Validity and Reliability of the Thai Version of the Gait Assessment and Intervention Tool (G.A.I.T.) - Jittima Saengsuwan; Patpiya Sirasaporn (Stroke Research and Treatment)
Introduction. The Gait Assessment and Intervention Tool (G.A.I.T.) is well-accepted for determining changes in gait quality in neurological patients. This study is aimed at translating the G.A.I.T. to Thai and to examine its validity and reliability. Methods. The Thai translation and back-translation into English were done according to international guidelines. Sixty-eight patients with subacute to chronic stroke were recruited. Concurrent validity was determined by the correlation coefficient between the Thai G.A.I.T. scale and a comfortable vs. fast gait speed. The convergent validity was determined by the correlation coefficient between the Thai G.A.I.T. and the lower extremity Motricity Index, the Functional Ambulation Category (FAC), and the National Institutes of Health Stroke Scale (NIHSS). Interrater reliability was assessed using videos of 68 patients analysed by two independent raters. Each rater was randomly assigned to rescore the Thai G.A.I.T. for each patient over at least two weeks to assess intrarater reliability. Results. The concurrent validity of the Thai G.A.I.T. vs. the respective comfortable and fast gait speeds was excellent (Rs=−0.79 and Rs=−0.68, p<0.001). The respective convergent validity with the lower extremity Motricity Index, NIHSS, and FAC was Rs=−0.62, 0.57, and -0.51, respectively. The respective inter- and intrarater reliabilities were excellent (ICC=0.93, 95% CI 0.88-0.96 and 0.95, 95% CI 0.91-0.97). Conclusion. A Thai version of the G.A.I.T. was developed, and its validity and reliability for use among patients with subacute to chronic stroke were established. Further work regarding the responsiveness of the tool is needed.